Knowledge, Attitude and Practice (KAP) of Malay Elderly on Salt Intake and Its Relationship With Blood Pressure - Hasnah Haron; NurAisyah Farhana Kamal; Hanis Mastura Yahya; Suzana Shahar (Frontiers Media S.A., 2021)
Hypertension is a worldwide problem and a major global health burden with high salt intake as one of the factors often related to it. Public exposure to a high salt diet has contributed to the increase in prevalence of hypertension among the Malaysian population. Improving the knowledge, attitudes and practices (KAP) related to salt intake is a key component of effective blood pressure control. Therefore, this study was aimed to determine the association of KAP of healthy salt intake toward blood pressure among the elderly residing in a semi urban area of Klang Valley Malaysia. A cross-sectional study using convenience sampling was conducted among Malay elderly, aged 60-81 years old residing in Bandar Baru Bangi. Subjects were required to answer the questionnaire via face to face interview regarding KAP of Salt Intake, together with sociodemographic and health profiles. Anthropometry parameters and blood pressure were measured. A total of 94 elderly [57.5% women with mean Body Mass Index (BMI) of 26. 46 ± 4.16, 42.5% men with mean BMI of 27.31 ± 5.19] have participated in the study. Results indicated that the overall KAP score was average (57.4%). However, majority showed a positive attitude toward reducing the salt intake. BMI was found to have significant correlation with blood pressure (r = 0.278, p < 0.05). Higher education level was significantly (p < 0.05) associated with good knowledge scores while younger subjects have a positive attitude toward healthy intake of salt (p < 0.05). Subjects with higher knowledge scores were also observed to have the more controlled blood pressure compared to those who scored less. Attitude and practices score showed no significance difference (p > 0.05) with blood pressure. Younger age, higher level of education and living partner or elderly was significantly (p < 0.05) associated with lower systolic and diastolic blood pressure. Overall, this study showed that knowledge toward healthy salt intake, BMI, education level, and living with others were significantly associated with the blood pressure among the elderly. Further education and intervention is required to improve knowledge on healthy salt intake among elderly as part of the prevention from hypertension.